Cybersecurity Strategies in Healthcare It Infrastructure: Balancing Innovation and Risk Management - Kami Yangzen Lama; Maham Saeed; Keya Karabi Roy; MD Abutaher Dewan (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
Due to the accelerated digitalization in the healthcare industry, clinical operations and the process of delivering care to patients have changed with the introduction of Electronic Health Records (EHRs), telemedicine platforms, cloud computing, and Internet of Medical Things (IoMT). This technological adaptation has however created cybersecurity vulnerabilities that are essential to the confidentiality, integrity, and availability of sensitive health information. In this paper, the author explores the twin dilemma of a contemporary healthcare institution: how to drive technology-related innovation and at the same time successfully mitigate cyber risks. Adopting a data-driven approach, the research synthesizes empirical evidence from recent cyber incidents, analyzes the effectiveness of global cybersecurity frameworks such as NIST and HIPAA, and evaluates emerging technologies' roles in risk mitigation. The methodology is based on the mixed-methods design, which consists of the case studies, incident data examination, and expert interviews, to provide the depth of analysis and practical significance. Findings indicate that despite the prospects of high-tech approaches to protection, including AI-based threat detection and blockchain-based data integrity, they require the support of solid governance policies, organizational training, and dynamic risk management models to achieve efficient protection. The received findings highlight the fact that strategic alignment of innovation and security is possible and, moreover, necessary to achieve the sustainability of digital healthcare transformation. The proposed study is novel since few studies have holistically approached the issue of cybersecurity strategies by providing a technological and organizational approach to the problem and providing recommendations that can be put into action by CIOs, policymakers and healthcare administrators. By filling in the gap between innovation and protection, the paper adds to an increasingly number of literatures that underlines the urgency of making cybersecurity a built-in aspect of the healthcare IT infrastructure.